Development and validation of a measurement tool for assessing municipal sports services in Buenos Aires Province, Argentina - Juan Carlos Sanchez; Aduna Badiola Lekue; Valentina Viego; Estibaliz Romaratezabala Aldasoro (Universidad de Murcia, 2024)
Drawing upon a literature review concerning the diagnosis, description, and evaluation of local sports, we formulated and validated a precise measurement instrument intended for characterizing the municipal sports services in the province of Buenos Aires (PBA), Argentina. The objective of the present study was to design and validate a measurement instrument for the characterisation of the municipal sports services of the PBA. We conducted a content validation process in two phases. In the first phase, the initial preliminary version of the instrument was reviewed and assessed by a panel of five experts, with a follow-up and adaptation by the research team. Afterwards, the final measurement instrument was evaluated by an expanded panel of 12 experts, showing high validity indexes (Aiken's V = 0.93) with figures greater than 0.9 in the lower extreme confidence intervals. In the second phase, to assess the reliability of the measurement instrument, a pilot study was carried out with 10 municipal sports offices from the PBA. Correlation coefficients of the test and retest responses greater than 0.9 were obtained, reflecting a high level of stability in the answers of the officials. The validated tool is a useful and reliable resource for managers of municipal sports services to operate with updated technical knowledge in decision-making. The instrument could be useful for the provincial authorities of the area, as it would allow to have a georeferenced characterisation of the sports supply and guide the local governments in the decision about sports interventions and the monitoring of the public sports service.